An agenda for cultural action and other essays - Panikkar, K. N. (Readings (Three Essays Press), 2006)
KN Panikkar focuses on the alliance between the neo-liberal economic policies and Hindu fundamentalism in India, its implication for civil society, and the destruction of the educational system through privatization and rabid communalization. He also discusses the historical context of the Hindu right wing cultural project and outlines the agenda for struggle against the corrosive influence of this homegrown fascism.